Forecasting model of air pollution index using generalized autoregressive conditional heteroskedasticity family (GARCH). - Zamrus, Nurul Asyikin; Mohd Rodzhan, Mohd Hirzie; Mohamad, Nurul Najihah (UTM Press, 2022)
The Air Pollution Index (API) of Malaysia has increased consistently in recent decades, becoming a serious environment issue concern. In this paper, we analyzed daily integer value time series data for API in Sarawak from January to June in 2019 using generalized autoregressive conditional heteroskedasticity (GARCH) family for discrete case namely Poisson integer value GARCH (INGARCH), negative binomial integer value GARCH (NBINGARCH) and integer value autoregressive conditional heteroskedasticity (INARCH) models. The parameters of the models will be estimated using quasi likelihood estimator (QLE) and we compare their Aiken information criterion (AIC) and Bayesian information criteria (BIC) to determine the best model fitted the data. Besides, the forecasting performance will be measured by using mean square error (MSE) and Pearson Standard Error (et). The results showed that INGARCH (1,1) and INARCH (1,0) performed inconsistent results since the conventional methods of NBINGARCH (1,1) outperformed the performance of INGARCH (1,1) and INARCH (1,0). However, consistent results were achieved as the NBINGARCH (1,1) gave the smallest forecasting error compared to INGARCH (1,1) and INARCH (1,0). The findings are very important for controlling the API results in future and taking protection measure for conservation of the air